Euforia Kemenangan Taliban dalam Bingkai Media Islam Indonesia: Studi Wacana Kritis Teun A. Van Dijk - Purnomo, Danang Try (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The study aims to describe the dimensions of the text of the Model Model Teun A Van Dijk in the discourse of opinion news text. The research is an online newspaper republika.com and nu.or.id in the form of opinion news texts about the Taliban's coup against the Afghan government. Data collection methods and techniques use documentation methods with listen and note techniques, while data analysis methods use content analysis methods with the critical discourse analysis approach of teun A Van Dijk model. The results found that the news contains three-dimensional text based on Teun A Van Dijk's theory, namely superstructure, macrostructure, and microstructure. From that dimension, it shows that the text of republika.com opinion has a keyakjinan preference that the Taliban can bring about better change for the Afghan government.Â Instead, the opinion text nu.or.id contained a preference for fears of Afghanistan's survival under the Taliban and vigilance for the world community about the adverse effects that could occur anywhere. The difference in perspective shows the subjectivity of a Â Â media in looking at a problem so as to represent the ideology of the media according to its social goals